Overview of gait rehabilitation in stroke - Sana Khalid; Arshad Nawaz Malik; Furqan Ahmed Siddiqi; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2023)
Stroke is the 2nd leading cause of death globally after ischaemic heart disease and is expected to rise more by 2030. The estimated incidence of stroke in Pakistan is about 250/100,000 individuals. Difficulty in walking is present in approximately 80% of stroke survivors. About a quarter of stroke survivors, even after receiving rehabilitation have residual gait impairments requiring assistance in activities of daily life. Almost half of stroke patients after being discharged will have episodes of fall, with majority of these falls occurring in activities like “turning”. Gait is one of the key features to participate in community and occupational activities. Therefore, appropriate gait rehabilitation post stroke is crucial for functional independence and community ambulation. There are many approaches to gait rehabilitation based on different models of motor physiology and disease. Augmenting conventional therapies with novel techniques such as utilization of electromechanical means have improved gait rehabilitation in improving functions. The usage of technology in rehabilitation of patients with neurological deficits, is still novel in Pakistan. This review provides an overview of advancements in neurological and gait rehabilitation post stroke. Keywords: Cerebrovascular accident, gait, muscle strength, rehabilitation, robotics, virtual reality.